Rehabilitation Surgery for Peripheral Facial Nerve Injury after Facial Trauma - Lam, An Quang; Tran, Thuy Phan Chung; Tran, Duong Van; Tran, Hiep Xuan; Fox, Albert J.; Tran, Luan Viet (International Archives of Otorhinolaryngology, 2024)
Introduction Facial trauma can cause damage to the facial nerve, which can have negative effects on function, aesthetics, and quality of life if left untreated.Objective To evaluate the effectiveness of peripheral facial nerve direct end-to-end anastomosis and/or nerve grafting surgery for patients with facial nerve injury after facial trauma.Methods Fifty-nine patients with peripheral facial nerve paralysis after facial injuries underwent facial nerve rehabilitation surgery from November 2017 to December 2021 at Ho Chi Minh City National Hospital of Odontology.Results All 59 cases of facial trauma with damage to the peripheral facial nerve underwent facial nerve reconstruction surgery within 8 weeks of the injury. Of these cases, 25/59 (42.3%) had end-to-end anastomosis, 22/59 (37.3%) had nerve grafting, and 12/59 (20.4%) had a combination of nerve grafting and end-to-end anastomosis. After surgery, the rates of moderate and good recovery were 78.4% and 11.8%, respectively. All facial paralysis measurements showed statistically significant improvement after surgery, including the Facial Nerve Grading Scale 2.0 (FNGS 2.0) score, the Facial Clinimetric Evaluation (FaCE) scale, and electroneurography. The rate of synkinesis after surgery was 34%. Patient follow-up postoperatively ranged from 6 to > 36 months; 51 out of 59 patients (86.4%) were followed-up for at least 12 months or longer.Conclusion Nerve rehabilitation surgery including direct end-to-end anastomosis and nerve grafting is effective in cases of peripheral facial nerve injury following facial trauma. The surgery helps restore nerve conduction and improve facial paralysis.
Keywords: facial paralysis; nerve anastomosis; nerve grafting; sural nerve; facial trauma